Symposium 1: Post COVID-19 World - Rusli, Mohammad Farhan (International Journal of Human and Health Sciences (IJHHS), 2022)
The COVID-19 pandemic that landed on Malaysian shores in January of 2019, was an event that is unbelievable, unexpected, ill-prepared and extremely underestimated. The pandemic exposed cracks and fractures that exist in our healthcare system and showed how fragile and vulnerable our public health infrastructure is. As Malaysians soldier on to what seems a knee-level muddy struggle in health, economy, and social well-being in a post-COVID-19 world, one must note that we must adapt and prepare in order to be resilient and be on-standby for future pandemics should they hit us again. Herewith lies the 5 pillars – digitalization of the healthcare system, integration of public health and clinical care, inter-agency collaboration, effective risk-communication, and most importantly, effective and strong governance. The first pillar focuses on the need to rapidly deploy and create a digital ecosystem that has a strong UI/UX base, both modifiable and adaptive in nature that is robust in facing any new developments in pandemic and public health challenges. The second pillar addresses the need to bridge the gap between public health services and clinical care for a seamless patient experience. The third pillar is the way forward on cutting through the bureaucracy that hinders effective implementation. The fourth pillar details the need of keeping order in chaos, enabling the people to understand and absorb trustable, reliable and accurate information. The fifth pillar is the cream of them all, where governance of the future will capture and effectively prepare the nation for a post-COVID-19 world with key policies, regulations and readied workforce. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S7